2018
DOI: 10.3389/fpls.2018.00208
|View full text |Cite
|
Sign up to set email alerts
|

Is the Success of Plant Invasions the Result of Rapid Adaptive Evolution in Seed Traits? Evidence from a Latitudinal Rainfall Gradient

Abstract: It has been widely suggested that invasion success along broad environmental gradients may be partially due to phenotypic plasticity, but rapid evolution could also be a relevant factor for invasions. Seed and fruit traits can be relevant for plant invasiveness since they are related to dispersal, germination, and fitness. Some seed traits vary along environmental gradients and can be heritable, with the potential to evolve by means of natural selection. Utilizing cross-latitude and reciprocal-transplant exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 79 publications
0
40
0
Order By: Relevance
“…Due to human activities, the co‐occurrence of salt and water stresses has become increasingly common (Dale, Jager, Wolfe, & Efroymson, ), and they pose severe threats to natural ecosystems (Setter & Waters, ; Touhami et al, ). Rapid evolution has been identified as an important mechanism that facilitates exotic plant invasion (Molina‐Montenegro et al, ; Poll et al, ). Despite extensive studies on plants responses to single stress, experimental studies that focused on the responses to combined stresses are very limited (reviewed by Mahalingam, ), especially those concerning invasive species (Stoler, Sudol, Mruzek, & Relyea, ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to human activities, the co‐occurrence of salt and water stresses has become increasingly common (Dale, Jager, Wolfe, & Efroymson, ), and they pose severe threats to natural ecosystems (Setter & Waters, ; Touhami et al, ). Rapid evolution has been identified as an important mechanism that facilitates exotic plant invasion (Molina‐Montenegro et al, ; Poll et al, ). Despite extensive studies on plants responses to single stress, experimental studies that focused on the responses to combined stresses are very limited (reviewed by Mahalingam, ), especially those concerning invasive species (Stoler, Sudol, Mruzek, & Relyea, ).…”
Section: Discussionmentioning
confidence: 99%
“…Intraspecific trait variation is the occurrence of a genotype expressing various phenotypes in a given environment; it's a combination of genetic (i.e., evolution) and environmental factors reflected in the variation within populations (forming ecotypes) (Valladares et al, 2007(Valladares et al, , 2014Turcotte and Levine, 2016;Barbour et al, 2018). Measuring intraspecific trait variation allows for an indepth understanding of a species' ability to respond and adapt to environmental changes (Molina-Montenegro et al, 2018). In this review, we focus on the average trait expression (reflected in functional traits) change in a single species spanning a large continental gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have shown that alien plants can undergo rapid evolution through trait adaptation to novel selection pressures (e.g. Molina-Montenegro et al 2018;van Boheemen et al 2019a;Lustenhouwer et al 2019;Brandenburger et al 2019a, b). Rapid trait adaptation may be driven by several processes; for example, the Evolution of Increased Competitive Ability (EICA) hypothesis posits that there is an evolutionary shift from costly defensive abilities to competitive performance in introduced populations, due to the absence of co-introduced specialist enemies (Blossey and Notzold 1995).…”
Section: Introductionmentioning
confidence: 99%